Elaeis guineensis - Kamyab, Hesam (IntechOpen, 2022)
Palm oil biomass is constantly produced in large quantities throughout the world as a waste product of the vast palm oil plantations. Biomass from the palm oil industry has been converted into value-added products to a limited extent via thermochemical, chemical, physical, and biochemical conversion routes. However, a significant amount of biomass, such as OPF and OPT, is still left in plantations. A pragmatic approach to converting them to value-added products will not only result in a cleaner environment but also generate significant revenue for the government. It is also suggested that more attention be paid to bioproducts in order to present them in an appealing form to end-users, thereby encouraging good patronage.